The Impact of Forced Migration on In-Group and Out-Group Social Capital - Anselm Hager; Justin Mattias Valasek (Center for Economic Studies and ifo Institute (CESifo), 2022)
In this paper, we study how forced migration impacts the in-group and out-group social capital of Syrian refugees and the host population in Northern Lebanon by administering a novel survey experiment in which we manipulate the salience of the migration experience (for refugees) and the refugee crisis (for the host population). Additionally, we study the social spillovers to Palestinians, an established refugee population in Lebanon. We find that the impact of forced migration is largely restricted to the Syrian refugee-Lebanese host population channel, and that it increases the relative disparity between in-group and out-group social capital. This may cause refugees to favor in-group interactions and therefore forgo more economically advantageous interactions with out-group members.
Keywords: C90; J15; D91; 330; refugees; migration; social capital; experiment; ethnicity